Peningkatan manajemen mutu terpadu di Lembaga Pendidikan Islam - Mispani, Mispani; Ikhwan Aziz Q; Ikhwanuddin, Ikhwanuddin; Ahmad Zarnuji; Yanuar Wicaksono; Tripitasari, Dika (Indonesian Journal of Educational Management and Leadership, 2023)
This article focuses on discussing total quality management in Islamic educational institutions. Teamwork in handling projects to improve or develop the quality of education is carried out through empowering employees and their work groups by giving them greater responsibility. The researcher uses a literature study conducted on several data findings from well-known journal publications such as Google Book, Google Scholar, Taylor & France, Elsevier, and other publications that discuss total quality management issues. To get answers to this research problem, researchers involved coding systems, data interpretation, and high-level evaluation to obtain valid and reliable data. The results of the research show that the existence of cooperation in an educational institution is the main capital in achieving quality and stakeholder satisfaction through a process of continuous quality improvement. Teachers, staff and everyone else in educational institutions also provide services to colleagues and fellow internal customers. Bad internal relations will hinder the development of an institution. Total Quality Management (TQM) transforms school institutions into a team to achieve one goal which is to satisfy all customers. The role of parents in motivating children from an early age is a big capital for children's success in school.